2020
DOI: 10.1111/1365-2745.13469
|View full text |Cite
|
Sign up to set email alerts
|

Plant protection services mediated by extrafloral nectaries decline with aridity but are not influenced by chronic anthropogenic disturbance in Brazilian Caatinga

Abstract: Most terrestrial species occur in human‐modified landscapes that are experiencing climate change. In addition to direct impacts on species, both anthropogenic disturbance and climate change can have important effects through changes in species interactions, including the disruption of ecological services provided by them. Here we investigate how chronic anthropogenic disturbance (CAD) and aridity affect the effectiveness of plant protection services provided by ants to plants bearing extrafloral nectaries (EFN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 85 publications
(178 reference statements)
1
21
1
Order By: Relevance
“…Previous studies in the Caatinga dry forest have reported a similar pattern, albeit with other diversity measures such as the taxonomic diversity of plants (Rito et al, 2017), functional and phylogenetic diversity of ants (Arnan, Arcoverde, et al, 2018), and ant-plant interactions (Câmara et al, 2018;Oliveira et al, 2019Oliveira et al, , 2020. In a sense, aridity seems to impose a higher selective pressure than disturbance at different levels of biological organization.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Previous studies in the Caatinga dry forest have reported a similar pattern, albeit with other diversity measures such as the taxonomic diversity of plants (Rito et al, 2017), functional and phylogenetic diversity of ants (Arnan, Arcoverde, et al, 2018), and ant-plant interactions (Câmara et al, 2018;Oliveira et al, 2019Oliveira et al, , 2020. In a sense, aridity seems to impose a higher selective pressure than disturbance at different levels of biological organization.…”
Section: Discussionsupporting
confidence: 62%
“…Such morphological variability is likely to represent a key asset by enabling individuals and populations to inhabit the immense variety of habitat provided by the Caatinga at the landscape and regional level. We refer to species with a high degree of generalist behavior relative to habitat use, food exploitation, and nesting (Hölldobler & Wilson, 1990;Leal et al, 2017), with potential impacts on community organization and structure, as well as the provision of ecosystem functions such as seed dispersal and plant protection against herbivores (Leal et al, 2017;Oliveira et al, 2019Oliveira et al, , 2020. This morphological variability may also represent a strategic asset for dealing…”
Section: Discussionmentioning
confidence: 99%
“…To characterise the rainfall gradient, mean annual rainfall within each plot was obtained from the WorldClim data base (http://www.worldclim.com.br) at a spatial resolution of 1 km. Because the rainfall and aridity indices were highly correlated ( r > .98), as observed by previous studies conducted in Catimbau NP (Arnan et al, 2018; Oliveira et al, 2021; Rito et al, 2017), we retained rainfall only as our measure of water deficit.…”
Section: Methodsmentioning
confidence: 99%
“…In this scenario, EFN traits would be favored in drier environments. On the other hand, Oliveira et al (2021) found that more aggressive ants interact more frequently with P . moniliformis plants in wetter rather than drier sites, which agree with RAH intra prediction of higher defense under higher resource availability (Figure 1b).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation